The structures of two aldazines: [1,1′-(1E,1′E)-hydrazine-1,2-diylidenebis(methan-1-yl-1-Ylidene) dinaphthalen-2-ol] (Lumogen) and 2,2′-(1E,1′E)-hydrazine-1,2-diylidenebis(methan-1-yl-1-ylidene)diphenol (salicylaldazine) in the solid state and in solution - Silva, Artur M. S. (2013)
A combination of NMR spectroscopy and theoretical methods Density functional theory including dispersion corrections (DFT-D) was used to study the structures of Lumogen and salicylaldazine. In the solid state, Lumogen exists as the dihydroxy tautomer 1andazine, C1⁄4N-N1⁄4C) as was already known from an X-ray determination. In a deuterated dimethyl sulfoxide solution, anothertautomer is observed besides 1a; its structure corresponds to the hydroxy-oxo tautomer 1b (a hydrazone, C1⁄4N NH Csp2). In whatconcerns salicylaldazine, we have observed only the dihydroxy tautomer 2a.